2014
DOI: 10.1590/s0102-67202014000100002
|View full text |Cite
|
Sign up to set email alerts
|

Influence of exercise testing in gastroesophageal reflux in patients with gastroesophageal reflux disease

Abstract: BackgroundGastroesophageal reflux disease is a worldwide prevalent condition that exhibits a large variety of signs and symptoms of esophageal or extra-esophageal nature and can be related to the esophagic adenocarcinoma. In the last few years, greater importance has been given to the influence of physical exercises on it. Some recent investigations, though showing conflicting results, point to an exacerbation of gastroesophageal reflux during physical exercises.AimTo evaluate the influence of physical activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 21 publications
1
6
0
1
Order By: Relevance
“…Menedes and colleagues concluded that light or short sessions of physical activity had no influence on reflux symptoms, but in the present study, the QOL of the patients was significantly improved. 17 In the present study, AE had positive effects on QOL without any significant change in LES pressure. Maybe change in mental aspects by AE improve the QOL of the patients.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Menedes and colleagues concluded that light or short sessions of physical activity had no influence on reflux symptoms, but in the present study, the QOL of the patients was significantly improved. 17 In the present study, AE had positive effects on QOL without any significant change in LES pressure. Maybe change in mental aspects by AE improve the QOL of the patients.…”
Section: Discussionsupporting
confidence: 52%
“… 15 Other studies conclude that moderate AE has no influence on reflux. 16 , 17 So, the aim of this study was to compare the effects of AE and DB on LES pressure and QOL of patients with reflux.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, only self-reported symptomatic gastric reflux was investigated and non-symptomatic reflux was, therefore, not taken into consideration. The influence from physical activity on gastroesophageal reflux has been discussed with contradictory opinions [46,47], but this was not investigated in this study. Several authors have reported that parental attitude and habits towards SDC and availability of soft drinks in school and at home affect consumption [3][4][5][14][15][16].…”
Section: Discussionmentioning
confidence: 95%
“…Mendes-Filho et al in Brazil performed a study involving 29 patients with GERD where they reported that patients had significant amount of acid reflux measured via continuous esophageal pH probes when they reached their VO2max of exercise tolerance (high-intensity exercise) on ergonomic stress testing. 16 Other studies refuted this observation, 17,18 whereas Djarv et al found that intermediate frequency of physical activity might decrease the risk of GERD in obese individuals (OR 0.41, 95% CI 0.22-0.27). 17 Given our findings in this study suggesting that physical activity does not reduce the risk of BE, and the mixed findings of studies of physical activity and the development of esophageal adenocarcinoma, it remains to be determined if physical activity affects the risk of progression from BE to esophageal adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Mendes‐Filho et al . in Brazil performed a study involving 29 patients with GERD where they reported that patients had significant amount of acid reflux measured via continuous esophageal pH probes when they reached their VO 2max of exercise tolerance (high‐intensity exercise) on ergonomic stress testing . Other studies refuted this observation, whereas Djarv et al .…”
Section: Discussionmentioning
confidence: 99%